Prolonged time of after-sensation after experimental pain stimuli despite efficient conditioned pain modulation in patients with chronic neuropathic pain after traumatic nerve injuries in upper extremity - Miclescu, Adriana (Pain Rep, 2021)
As yet, there is limited research that can identify factors that differentiate between painful and nonpainful neuropathies after traumatic nerve injury. The aim of this study was to compare subjects with pain and without pain, all after operative nerve repair in the upper extremities. METHODS: Subjects in both groups (pain, n = 69; painless, n = 62) underwent clinical assessment of sensory nerve function and psychophysical tests: quantitative sensory testing and conditioned pain modulation (CPM). Conditioned pain modulation was assessed by pain ratings to 120 seconds pressure stimuli administered before and after a 60 seconds noxious 4°C cold conditioning stimulus (CS). Time of recovery (time off) of pain intensity from peak VAS(maxc) after CS was recorded. Questionnaires about the quality of life (RAND-36) and disability of the extremity (QuickDash) were completed. RESULTS: There were no significant differences between groups for CPM (P = 0.19). Time off was 42 seconds in subjects with pain in comparison with 28 seconds in those without pain (P < 0.0001). Compared with individuals reporting no pain, participants with neuropathic pain after nerve injuries had 1.8 times the odds of recovering later after CS, gain of function findings at sensory examination (P < 0.0001), lower scores of the physical component of RAND-36 (P < 0.0001), and increase arm disability (P < 0.0001). Hyperesthesia to cold pain stimulation (P = 0.03) and lowered pain pressure threshold (P = 0.01) were found in the pain group. CONCLUSION: Recovery after the pain induced by cold CS indicates changes in central processing of pain and provides a potential measurement of endogenous pain modulation in individuals with chronic neuropathic pain.